Preventive HIV vaccine acceptability and behavioral risk compensation among high-risk men who have sex with men and transgenders in Thailand - Peter A. Newman (2018)
Thailand, with the highest number of volunteers to have participated in preventive HIV-1 vaccine trials globally, may be an early adopter of HIV vaccines. We conducted a mixed methods investigation, including 30 in-depth interviews and a venue-based survey. We used a structured questionnaire including conjoint analysis and a fractional factorial experimental design to assess preventive HIV vaccine acceptability and risk compensation among 255 high-risk men who have sex with men (MSM) and transgenders (mean age = 26.6 years). HIV vaccine acceptability ranged from 31.6 to 73.8 on a 100-point scale; mean = 58.3 (SD = 17.1). Vaccine-induced seropositivity (VISP) had the greatest impact on acceptability, followed by efficacy, side effects, duration of protection, out-of-pocket cost and social saturation. Over one-third (34.6%) reported intentions to increase post-vaccination risk behaviors in response to a highly efficacious HIV vaccine. Social and structural interventions to promote HIV vaccine uptake as a prosocial behavior, provide accessible assays to detect VISP, and subsidize vaccine costs, and support for uptake of partially efficacious vaccines in the context of combination prevention, will facilitate HIV vaccine dissemination in Thailand. © 2009 Elsevier Ltd. All rights reserved.